HOLOGRAPHIC VISUALIZATION OF CYLINDRICAL PIEZOCERAMIC TRANSDUCERS VIBRATIONS - R. Vasiliauskas; K. Ragulskis; L. Patašien; A. Fedaravičius (Приборы и методы измерений, 2015)
The piezomaterial used in cylindrical piezoceramic transducers vibrations requiring high precision displacements indicates that accuracy depends on design and technological factors. The analyzed criteria have made possible to choose the piezomaterial for optimal mechatronic system having a maximal displacement. The experimental investigation of precision vibrosystems by means of 3D holographic visualization enables one to obtain appreciably larger amount of information about the vibrating surface in comparison with traditional methods. On the basis of the developed methodology of analyzing the experimental data derived from 3D holographic visualization and by using the experimental holography stand, we have obtained results making it possible to optimize the design of operation of the piezoceramic mechatronic system or its separate elements.